2013
DOI: 10.1080/19443994.2012.695045
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of PCBs and heavy metals in water of the dam reservoir and use of pre-hydrolyzed coagulants to micropollutants removal from surface water

Abstract: A B S T R A C TThe aim of the presented research work was to analyze the pollution in the Kozłowa Gó ra Dam Reservoir (Poland) with indicative Polychlorinated biphenyls (PCBs) (28, 52, 101, 118, 138, 153, 180) and heavy metals (Zn, Cu, Ni, Cd, Pb, Cr). Aluminum sulfate and pre-hydrolyzed polyaluminium chloride (PAX-XL1, PAX-XL19) were used as coagulants, and the following parameters were analyzed in the water samples from the Kozłowa Gó ra Dam Reservoir: turbidity, color, and concentrations of PCBs and heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…(2014) [1][2][3][4][5][6][7] www.deswater.com doi: 10.1080/19443994.2014.982957 control reservoirs (10.0%) or for recreation (5.3%). Most issues concern the use of reservoir water for drinking, as most of surface water is polluted to some degree.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…(2014) [1][2][3][4][5][6][7] www.deswater.com doi: 10.1080/19443994.2014.982957 control reservoirs (10.0%) or for recreation (5.3%). Most issues concern the use of reservoir water for drinking, as most of surface water is polluted to some degree.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Most issues concern the use of reservoir water for drinking, as most of surface water is polluted to some degree. River water flowing into reservoirs contains municipal [3], agricultural [4] or industrial contaminants [5]; most frequently, these are mixed contaminants coming from multiple sources [6,7]. Additionally, many reservoirs are exposed to eutrophication processes [8][9][10].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Then 0.7 dm 3 of water was decanted. Before and after the coagulation process, water analysis was performed, including determination of: pH, turbidity, colour, total organic carbon (TOC), and PCB analysis [12].…”
Section: Coagulation Processmentioning
confidence: 99%
“…Research conducted in 2009-2011 for chosen water reservoir in Poland, which is the source of water for water treatment plant, showed that the water and the bottom sediments are contaminated with PCB [12]. The scope of PCB concentration in the reservoir water ranged from 1.0 to 8.1 ng/dm 3 , whereas the concentration of these compounds in the bottom sediments ranged from 0.12 to 2.78 µg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Where results are available, these indicate a need for process parameters to be selected separately for each type of substance. Furthermore, a key aspect of any process to achieve the oxidation of organic contaminants is the possibility that intermediate products (including some more toxic than the parent) may be formed [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%